Kedaulatan Allah Dalam Konteks Kehidupan Praktis Orang Kristen - Amazihono, Yakub Efraim; Manu, Charisal B.S. (Vieka Wahana Semesta, 2024)
The sovereignty of God is a classic topic that is always relevant when faced with the many challenges and obstacles experienced by every human being. For example, in human life, especially believers. Sometimes God is always there despite the fact that mankind does not care about Him. It is almost the same as what happened in the OT era where the Israelites did not care about the love that God gave them but God still continued to take care of His people. This is quite a unique thing why God always keeps His power over His people even though He is often ignored by His people. Therefore, the discussion below is about the sovereignty of God or the totality of God in guarding and protecting His people.